Level of Knowledge, Understanding, and Impact of the COVID-19 Pandemic on Continuing Fixed Orthodontic Treatment in Adults: A Questionnaire Study. Issue 2 (April 2021) - Ram, RSVM Raghu; Ranganayakulu, I; Viswanadh, K Anand; Kumar, TSS Manikanta; Chaitanya, C Viswa; Sunil, G.
Objectives: To evaluate the level of knowledge, understanding, and impact of the coronavirus disease 2019 (COVID-19) pandemic on adult patients regarding their ongoing fixed orthodontic treatment. Subjects and Methods: A cross-sectional and descriptive survey was conducted on 108 adult patients undergoing fixed orthodontic treatment at GSL Dental College (GSLDC), India. All the candidates were aged 18 years and above, who were in lockdown due to the COVID-19 pandemic and devoid of treatment. Results: Among the patients 43.5% were male and 56.5% were female; 22.3% were not at all aware that the COVID-19 virus spreads quickly in a dental setup; 64.8% were definitely willing for their status disclosure and to undergo pretreatment screening; 71.3% were definitely willing to adhere to strict appointment timings for adequate sanitization of the clinical area; 60.2% thought that missed appointments during the COVID-19 pandemic would prolong their overall orthodontic treatment and affect their treatment outcome; and 51.9% were financially affected due to the pandemic. Conclusions: Not all adult orthodontic patients were in knowledge of COVID-19 cross infection. The majority were in a state of understanding and willing to follow infection-eradicating protocols. Patients' view on overall orthodontic treatment was altered due to the psychological and financial impact of COVID-19.